Household water sharing: A review of water gifts, exchanges, and transfers across cultures. (7th September 2018) - Wutich, Amber; Budds, Jessica; Jepson, Wendy; Harris, Leila M.; Adams, Ellis; Brewis, Alexandra; Cronk, Lee; DeMyers, Christine; Maes, Kenneth; Marley, Tennille; Miller, Joshua; Pearson, Amber; et al.
Abstract : Water sharing offers insight into the everyday and, at times, invisible ties that bind people and households with water and to one another. Water sharing can take many forms, including so‐called "pure gifts, " balanced exchanges, and negative reciprocity. In this study, we examine water sharing between households as a culturally embedded practice that may be both need‐based and symbolically meaningful. Drawing on a wide‐ranging review of diverse literatures, we describe how households practice water sharing cross‐culturally in the context of four livelihood strategies (hunter‐gatherer, pastoralist, agricultural, and urban). We then explore how cross‐cutting material conditions (risks and costs/benefits, infrastructure and technologies), socioeconomic processes (social and political power, water entitlements, ethnicity and gender, territorial sovereignty), and cultural norms (moral economies of water, water ontologies, and religious beliefs) shape water sharing practices. Finally, we identify five new directions for future research on water sharing: conceptualization of water sharing; exploitation and status accumulation through water sharing, biocultural approaches to the health risks and benefits of water sharing, cultural meanings and socioeconomic values of waters shared; and water sharing as a way to enact resistance and build alternative economies. This article is categorized under: Human Water > Value of Water Human Water > Rights to Water Abstract : Cross‐cutting factors that shape water sharing between households